High-performance apparel materials, development, and applications - McLoughlin, John; Sabir, Tasneem (Duxford, United Kingdom Woodhead Publishing, 2017)
High-Performance Apparel: Materials, Development, and Applications covers the materials and techniques used in creating high-performance apparel, the technical aspects of developing high-performance garments, and an array of applications for high-performance clothing and wearable technology. Part One covers fabric construction for high-performance garments, from fiber types and spinning methods, to weaving, knitting, finishing, and joining techniques. Development of high-performance apparel is covered in Part Two, with particular emphasis on design and product development for function and wearer comfort. Part Three covers a range of applications and wearable technology that make use of high-performance apparel, including chapters on sportswear, protective clothing, and medical, military, and intelligent textiles. The book provides an excellent resource for all those engaged in garment development and production, and for academics engaged in research into apparel technology and textile science.--Provided by publisher.
1. Introduction to high-performance apparel -- Part I High-performance fabric, materials and manufacture -- 2. Fibers used for high-performance apparel -- 3. Advances spinning methods for high-performance apparel -- 4. Advances weaving technologies for high-performance apparel -- 5. Advanced knitting technologies for high-performance apparel -- 6. Functional finishes for high performance textiles -- 7. Joining techniques for high-performance apparel -- 8. Testing of high performance fabrics for apparel -- Part II Developing high-performance garments -- 9. Designing high-performance apparel from concept to garment -- 10. New product development in high-performance apparel -- 11. Anthropometrics used in high-performance apparel development -- 12. Body scanning and measurement in high-performance apparel -- 13. Comfort and durability in high performance clothing -- Part III Applications of high-performance apparel and wearable technology -- 14. Future textiles for high performance apparel -- 15. Electronics used in high performance apparel -- 16. Revolutions in wearable technology for apparel -- 17. High-performance sportswear -- 18. High-performance apparel for protection -- 19. Composite textiles used in high-performance apparel -- 20. Conductive fibers and their role in high-performance apparel -- 21. High performance apparel for outdoor pursuits -- 22. Microchip technology used in textile materials -- 23. High-performance apparel for military applications -- 24. High-performance apparel for medical professionals.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Textile fabrics -- Technological innovations; Smart materials; Clothing and dress -- Technological innovations; Electronic books